Dr. B.B. Mundkar Memorial Lecture of 2007 - C. MANOHARACHARY - MANOHARACHARY*, C. (Indian Phytopathology, 2008)
The number of fungi recorded in India exceeds 28,000 species, the largest biotic community recorded after insects. These organisms are without plastids, nutrition absorptive, never phagrotrophic, without an amoeboid pseudopodial phase, cell walls containing chitin and Ã¢-glucans mostly, mitochondria with flattened cristae, peroxisomes nearly present. Individual assternae present, thallus being unicellular or filamentous and consisting of multicellular coenocytic, haploid hyphae reproducing sexually or asexually, the diploid phase generally short lived, saprobic, mutualistic or parasitic. Water is a mobile medium and a transporting vehicle for fungi. Zoosporic fungi colonize diverse habitats in fresh water and help in recycling of organic matter, energy budget, and food chain besides the disease production. It comprises Chytridiomycetes, Hyphochytridiomycetes and Oomycetes. This group consists of 200 genera and 1160 species. Physicochemical factors like pH, temperature, altitude, water flow; depth, aerobic nature, pollutants, vegetation, macro and microelements are known to influence their biodiversity status, distribution, seasonal variation and activity. The available taxonomic information on water-borne conidial fungi from Indian sub-continent is far from satisfaction. Reliable quantitative and qualitative information are essential to fill up the lacunae in the existing knowledge. Extensive surveys have to be made in order to understand the diversity and distribution patterns of this group of fungi growing under Indian conditions. Further studies on culturing, on the ecology and physiology of water-borne conidial fungi are necessary besides studying the role of these fungi in aquatic eco-system.